Mapping Phalaris minor under the Rice-Wheat Cropping System in different Agro-Ecological Regions of Nepal - Ranjit, JD; Bellinder, RR; Hobbs, P; Rajbhandari, NK; Kataki, P (Nepal Agriculture Research Journal, 2009)
A survey was conducted in order to map the spread of Phalaris minor in wheat in nine districtsin the mid-hill, Terai and inner Terai areas of the rice-wheat cropping system in Nepal during1998/99. Both qualitative and quantitative data were collected from 540 farmers and P. minorwas recorded in all of the nine surveyed districts. Percent summed dominance ratio (SDR) andaverage number per unit area (m2) of P. minor was compared to different districts of mid-hills,inner Tarai, and Tarai belts along with other weeds in the wheat crop. P. minor ranked as thefirst and second important weed of wheat that reduced the wheat yield from 10 to 50 percent. Itspopulations varied from district to district. However, the infestation appeared to be in increasingtrend. Future strategies need to consider in increasing growers' abilities to identify P. minor atearly growth stages when it is particularly difficult to differentiate from wheat seedlings. It issuggested that frequent monitoring of weeds in different tillage and weed management practicesshould be initiated. Besides farmers' training in the future there needs to be emphasis placed onincreasing farmer's awareness on the serious negative impact of P. minor on wheat yield andquality.Key words: Agro-ecology; Phalaris minor; survey; weeds; wheatDOI: 10.3126/narj.v7i0.1869Nepal Agriculture Research Journal Vol.7 2006 pp.54-63